Optimizing Arabic Reading Comprehension Skills through the Quizizz App: An Interactive Learning Breakthrough for Higher Education - Zaharo Zaharo; Laily fitriani; Renni Hasibuan (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2024)
This study aims to determine the use of the Quizizz application in learning Arabic to improve maharah Qiro'ah which will be used as a diverse and fun learning alternative that includes planning, use and evaluation. This research is a qualitative research approach with descriptive methods. The data used is in the form of information sourced from second semester students in class B majoring in Arabic Language and Literature, State Islamic University of Maulana Malik Ibrahim Malang. Data collection techniques used observation, interviews and documentation. As for the data analysis technique used in this study using the data analysis model developed by Miles & Huberman: namely data collection, condensation, data presentation, and drawing conclusions. The results of this study are that this application is very relevant and very supportive for Arabic learning assessment activities, especially in maharoh Qiro'ah. Likewise, with the use of this application, learning outcomes increase which can make it easier for students to understand the material, learning becomes more fun, increasing motivation and interest students and their independence, and students are more active in learning. Although not all of Quizizz's free features can be used as a means of evaluation media and can be complained about with interactive learning materials.